2016
DOI: 10.17795/ccn-10294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foot Reflexology Massage and Foot Bath on the Sleep Quality of Patients with Acute Coronary Syndrome: A Comparative Study

Abstract: Objectives: Cardiovascular diseases, especially coronary artery diseases, result in sleep disturbance. Myocardial muscle oxygen demand rises in sleep disturbance. Also, the possibility of cardiovascular risks such as re-infarction and dysrhythmias increases. As a result, removing sleep disorders is very important. The current study aimed at assessing the effect of foot reflexology massage and foot bath methods on sleep quality of the patients with acute coronary syndrome (ACS) through a comparative study. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
8
1
1
Order By: Relevance
“…Our findings are in contrast with the findings of a systematic review on the effect of earplugs and eye masks on quality of sleep in the ICU [7], in which, out of 18 studies [11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] that evaluated subjective sleep quality using questionnaires, 17 [11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36] found improvements in sleep quality with the use of earplugs and eye masks, and only one study [35] did not find any improvement. These studies, however, were conducted in critically ill patients in an ICU setting [20][21][22][23][24][25][26][27][28][29][...…”
Section: Discussioncontrasting
confidence: 97%
“…Our findings are in contrast with the findings of a systematic review on the effect of earplugs and eye masks on quality of sleep in the ICU [7], in which, out of 18 studies [11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] that evaluated subjective sleep quality using questionnaires, 17 [11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36] found improvements in sleep quality with the use of earplugs and eye masks, and only one study [35] did not find any improvement. These studies, however, were conducted in critically ill patients in an ICU setting [20][21][22][23][24][25][26][27][28][29][...…”
Section: Discussioncontrasting
confidence: 97%
“…The authors suggested warm footbath may have a positive impact on pain relief. Considering the decreased sleep quality in patients hospitalized in CCUs, Naseri et al (2016) evaluated the effect of foot reflexology massage and foot baths on the sleep quality of patients with acute coronary syndrome. The authors concluded that a footbath and foot massage alone can enhance sleep quality in patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study which was conducted by Kheyri et al, the results were similar to our results: the mean post‐test scores of elderly women who did not have reflexology after abdominal surgery increased while their sleep quality decreased (Kheyrı, Bastanı, & Haghanı, ). Naseri et al found that patients with acute coronary syndrome had a decreased sleep quality when they were not given reflexology and foot baths (Naseri, Rahmani, Nerir, Salari, & Farahani, ). In the studies cited, it was found that sleep quality decreases in patients who were not given reflexology, yet the results of our study are compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%